The Arabidopsis mitogen-activated protein kinase 6 is associated with γ-tubulin on microtubules, phosphorylates EB1c and maintains spindle orientation under nitrosative stress - Kohoutová, Lucie; Kourová, Hana; Nagy, Szilvia K; Volc, Jindřich; Halada, Petr; Mészáros, Tamás; Meskiene, Irute; Bögre, László; Binarová, Pavla (The New phytologist, 2015)
Stress-activated plant mitogen-activated protein (MAP) kinase pathways play roles in growth adaptation to the environment by modulating cell division through cytoskeletal regulation, but the mechanisms are poorly understood. We performed protein interaction and phosphorylation experiments with cytoskeletal proteins, mass spectrometric identification of MPK6 complexes and immunofluorescence analyses of the microtubular cytoskeleton of mitotic cells using wild-type, mpk6-2 mutant and plants overexpressing the MAP kinase-inactivating phosphatase, AP2C3. We showed that MPK6 interacted with γ-tubulin and co-sedimented with plant microtubules polymerized in vitro. It was the active form of MAP kinase that was enriched with microtubules and followed similar dynamics to γ-tubulin, moving from poles to midzone during the anaphase-to-telophase transition. We found a novel substrate for MPK6, the microtubule plus end protein, EB1c. The mpk6-2 mutant was sensitive to 3-nitro-l-tyrosine (NO2 -Tyr) treatment with respect to mitotic abnormalities, and root cells overexpressing AP2C3 showed defects in chromosome segregation and spindle orientation. Our data suggest that the active form of MAP kinase interacts with γ-tubulin on specific subsets of mitotic microtubules during late mitosis. MPK6 phosphorylates EB1c, but not EB1a, and has a role in maintaining regular planes of cell division under stress conditions.
Keywords: Tubulin; Stress, Physiological; aparát dělícího vřeténka; telofáze; proliferace buněk; Plant Cells; mikrotubuly; Arabidopsis Proteins; nitrosative stress; anafáze; segregace chromozomů; mitogen-activated protein kinase; Mitogen-Activated Protein Kinases; meristém; Tyrosine; kinetochory; MPK6; Butadienes; proteiny huseníčku; fyziologický stres; Telophase; proteiny asociované s mikrotubuly; Nitrosation; tubulin; rostlinné buňky; fosforylace; nitrily; mitogenem aktivované proteinkinasy; Nitriles; microtubules; γ-tubulin; Cell Proliferation; butadieny; tyrosin; Spindle Apparatus; Anaphase; Microtubules; Arabidopsis; Microtubule-Associated Proteins; EB1c; cytokineze; cell division; nitrosace; Chromosome Segregation; Cytokinesis; Kinetochores; extracelulárním signálem regulované MAP kinasy; Meristem; Phosphorylation; Extracellular Signal-Regulated MAP Kinases